Impact of Caring for Terminally Ill Children on Physicians: A Systematic Scoping Review. (April 2021) - Ngiam, Lisa Xin Ling; Ong, Yun Ting; Ng, Jun Xuan; Kuek, Joshua Tze Yin; Chia, Jeng Long; Chan, Natalie Pei Xin; Ho, Chong Yao; Abdurrahman, Ahmad Bin Hanifah Marican; Kamal, Nur Haidah Ahmad; Cheong, Clarissa Wei Shuen; Ng, Cheng Han; Tan, Xiu Hui; et al.
Introduction: Caring for terminally ill children influences nurses' and allied health provider's quality of life, ability to provide personalized, dignified and empathetic care and even their concepts of personhood. In the absence of data this review utilizes the Ring Theory of Personhood (RToP) to evaluate how a physician's concept of personhood is affected caring for terminally ill children in order to better support them holistically. Methods: Using PRISMA Guidelines, 14 researchers carried out independent searches of PubMed, CINAHL, PsycINFO, Cochrane Library and gray literature databases for articles published between 2000 to 2019. Concurrent and independent employment of content and thematic analysis (Split Approach) was used to enhance the trustworthiness of the analysis. Results: 13, 424 titles and abstracts were retrieved, 188 full texts were evaluated, and 39 articles were included and analyzed. Identical categories and themes identified using the Split Approach suggest that caring for dying children in PPC impacts the physician's professional identity, clinical decision making, personal well-being and relationships. The data also suggests that the magnitude of these effects depends on the presence of protective and risk factors. Conclusion: Aside from providing a novel insight into the upon the physician, this review proffers a unique approach to accounting for the presence, magnitude and influence of incoming catalysts, resultant conflicts, and protective and risk factors upon the physician's personhood. Further studies into the changes in personhood are required. Design of a personalized assessment tool based on the RToP will help direct timely, appropriate and personalized support to these physicians.